57 Self-managed Loaded Exercise Versus Usual Physiotherapy Treatment For Rotator Cuff Tendinopathy: A Randomised Controlled Trial (the Self Study). (5th September 2014) - Littlewood, Chris; Mawson, Sue; May, Stephen; Walters, Stephen
Abstract : Introduction: Shoulder pain is the third most common reason for consultation with a physiotherapist and disorders of the rotator cuff are thought to be the commonest cause of this pain. Despite this commonality and burden, rotator cuff tendinopathy is a poorly understood condition with a dearth of high quality studies informing optimal management. A range of interventions, both conservative and surgical, are currently used to treat this condition [Littlewood et al. 2012a]. Although the mechanism of action is poorly understood [Littlewood et al. 2013], the potential benefits of loaded exercise, i.e. exercise against gravity or resistance, in comparison to other conservative or surgical treatment strategies have been reported in a systematic review [Littlewood et al. 2012b]. The aim of this study was to evaluate the clinical effectiveness of a self-managed loaded exercise programme versus usual physiotherapy treatment for rotator cuff tendinopathy. Methods: A multi-centre pragmatic unblinded parallel group randomised controlled trial was conducted with eighty-six patients with a clinical diagnosis of rotator cuff tendinopathy, recruited across three NHS centres. The primary outcome measure was the Shoulder Pain and Disability Index (SPADI) at three months. Secondary outcomes measures included the SPADI at six months and the SF-36 at three and six months. Analysis of covariance was used to compare mean total scores between the groups at three and six month's post-randomisation, adjusted for baseline score. Results: There were no statistically significant differences between the groups across all outcomes at three months. By six months there remained no significant difference between the groups across most outcomes except the SPADI pain subscale demonstrated statistical and clinically significant difference in favour of the self-managed exercise group (p < 0.05). Discussion: Both the self-managed loaded exercise programme and usual physiotherapy treatment appear to be effective interventions for rotator cuff tendinopathy. But, this RCT does not provide sufficient evidence of superiority of one intervention over the other in the short-term. Also, in the mid-term, this RCT does not provide sufficient evidence of superiority except in relation to shoulder pain where a statistical and clinically significant difference in favour of the self-managed exercise group was demonstrated. However, these findings need to be considered in the context of a relatively high loss to follow-up which might confound the validity of these conclusions. References: Littlewood, et al . Shoulder & Elbow. 2012a;4:64–71 Littlewood, et al . Physiother . 2012b;98:101–109 Littlewood, et al . Man Ther . 2013;18:468–472